2016
DOI: 10.1080/01480545.2016.1199563
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on thein vitrocytotoxic responses of two mammalian cell types to fullerenes, carbon nanotubes and iron oxide nanoparticles

Abstract: The present study was designed to evaluate and compare the time- and dose-dependent cellular response of human periodontal ligament fibroblasts (hPDLFs), and mouse dermal fibroblasts (mDFs) to three different types of nanoparticles (NPs); fullerenes (C), single walled carbon nanotubes (SWCNTs) and iron (II,III) oxide (FeO) nanoparticles via in vitro toxicity methods, and impedance based biosensor system. NPs were characterized according to their morphology, structure, surface area, particle size distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 73 publications
3
12
0
Order By: Relevance
“…Since NR assay is based on the ATPdependent lysosomal incorporation of the supravital dye and the measurement of the fluorescence of the incorporated dye [43], the apparent increase in the viability given by NR assay is most probably the result of an increased lysosomal compartment due to the IOMNPs exposure and intra-lysosomal incorporation. Dissimilarities between viability assays that evaluate different mechanisms of toxicity were previously reported, reiterating the need for multiple viability assays when evaluating the cytocompatibility/cytotoxicity of nanomaterials [64,65]. Similar to the results obtained in this study, a slight decrease in the cellular viability, measured by the WST assay -an assay similar to Alamar Blue -, and an increase in the NR-dye uptake upon exposure to IOMNPs were previously reported [44].…”
Section: Cytocompatibility Of Magnetite Nanoparticles (Iomnps)supporting
confidence: 87%
“…Since NR assay is based on the ATPdependent lysosomal incorporation of the supravital dye and the measurement of the fluorescence of the incorporated dye [43], the apparent increase in the viability given by NR assay is most probably the result of an increased lysosomal compartment due to the IOMNPs exposure and intra-lysosomal incorporation. Dissimilarities between viability assays that evaluate different mechanisms of toxicity were previously reported, reiterating the need for multiple viability assays when evaluating the cytocompatibility/cytotoxicity of nanomaterials [64,65]. Similar to the results obtained in this study, a slight decrease in the cellular viability, measured by the WST assay -an assay similar to Alamar Blue -, and an increase in the NR-dye uptake upon exposure to IOMNPs were previously reported [44].…”
Section: Cytocompatibility Of Magnetite Nanoparticles (Iomnps)supporting
confidence: 87%
“…Different cellular systems have different rates of cellular uptake and can alter the mechanisms of the uptake process. 7,26,39,73 CNT internalization by human lung cancer cells A549, human lung cancer cells Calu-6, human breast cells MCF-7, and mouse macrophage cells J774 have been studied by Summers et al 68 . They found that CNT uptake was the highest in the J774 cell line.…”
Section: Cell Typementioning
confidence: 99%
“…Similar results were found for gold nanoparticles embedded in amphiphilic block copolymers. 38 AuNPs are essentially harmless compared to other antimicrobial nanoparticles, such as zinc nanoparticles, which have a substantial toxic impact on human fibroblast after 24 h. 39 This demonstrates that the proposed photosensitizer is selectively toxic for bacteria and does not affect eukaryotic cells to any significant extent, due to the absence of any penicillin-binding protein 1A on the eukaryotic membrane.…”
Section: Resultsmentioning
confidence: 97%